European Paediatric Surgeons' Association Consensus Statement on the Management of Giant Omphalocele - Saxena, Amulya K.; Hayward, Romilly K.; Mutanen, Annika; Goneidy, Ayman; Ghattaura, Harmit; Gorter, Ramon; Weijnen, Rene; Keijzer, Richard; Soyer, Tutku; The European Pediatric Surgeons' Association (European Journal of Pediatric Surgery, 2025)
Giant omphalocele management had not reached a consensus from the pediatric surgical perspective regarding conservative treatments, surgical approaches, and clinical outcomes. This topic was therefore selected for the 2023 Consensus Session of the European Paediatric Surgeons' Association (EUPSA).Literature review was conducted by seven EUPSA members, guided by a set of predefined areas relating to the management of giant omphalocele: (1) conservative management, (2) surgical management, and (3) outcomes. Members were assigned to specific topics, with discrepancies resolved through structured group discussion and further literature review. Consensus was reached through unanimous agreement among the contributing members. Each topic was presented with available evidence to congress participants. Comments from participants were accounted to formulate the final consensus statement.Giant omphalocele is appropriately defined as viscero-abdominal disproportion preventing primary closure. Regarding (1) conservative management, the “paint and wait” approach is recommended when anatomical constraints or high surgical risk preclude primary closure. Common painting agents include povidone-iodine and silver sulfadiazine, with Manuka honey gaining interest, though consensus on dosing, duration, and complications remains unclear. With regards to (2) surgical management, early closure favors biological meshes, while delayed closure appears most effective using native tissues. High mortality in delayed patch closure likely reflects a population with the most severe defects. Finally, (3) outcomes highlights key prognostic factors including chromosomal abnormalities, cardiac defects, and low birth weight, which may guide counseling, screening, and treatment. Limited data on ruptured omphalocele indicates towards increased mortality, necessitating prompt intervention. Complications following management are relatively rare and typically intervention-related, underscoring the need for long-term, multidisciplinary follow-up.A consensus statement on the management of giant omphalocele was developed based on current evidence and peer practice, though imitations relating to a scarcity of high-level evidence and significant heterogeneity across studies should be acknowledged. Despite these constraints, this consensus statement provides evidence-based guidance to support pediatric surgeons in informed decision-making for this pathology.
Keywords: consensus statement; giant omphalocele; surgical management; conservative treatment; outcomes